EDUCATION IN THE PROVINCE OF QUEBEC (Author: R. Magnuson) - Bradley, J. G. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1975)
R. Magnuson. EDUCATION IN THE PROVINCE OF QUEBEC. Montreal: McGill University Printing Services, 1974. 91 pp. 2.25.